Nonlinear output feedback control of dynamically positioned ships using vectorial observer backstepping - Fossen, T.I.; Grovlen, A. (IEEE transactions on control systems technology, 1998)
Dynamic positioning (DP) systems for ships are usually designed under the assumption that the kinematic equations be linearized about a constant yaw angle such that linear and gain scheduling techniques can be applied. This paper proposes a globally exponentially stable (GES) nonlinear control where this assumption is removed. A nonlinear observer is included in the design such that only position measurements are required. GES is proven by applying the backstepping design methodology and Lyapunov stability theory. The control law is simulated on two thruster-controlled ships.